Biologic and Checkpoint Inhibitor‐Induced Liver Injury: A Systematic Literature Review. Issue 2 (2nd January 2020) - Shah, Parth; Sundaram, Vinay; Björnsson, Einar
Abstract : Biologics are among the most commonly prescribed medications for several chronic inflammatory diseases. Tumor necrosis factor alpha inhibitors, more so than other agents, have been observed to cause drug‐induced liver injury. Additionally, because the approval and popularity of checkpoint inhibitors have grown, similar patterns of liver injury have been documented, with a majority of cases describing immune‐mediated hepatitis. Although the exact mechanism of injury is unknown, various host and medication characteristics play a role in the outcome of the molecular cascade invoked by biologics. Prognosis is usually favorable with cessation of the offending agent, but cases of acute liver failure requiring liver transplantation have also been observed. Therefore, algorithms have been created to assist clinicians in treating drug‐induced autoimmune hepatitis, mostly with corticosteroids. Additionally, case reports have documented successfully rechallenging patients with a different biologic without recurrence of liver injury, but data are limited. Further investigation is warranted regarding the potential for cross‐reactivity and mechanism of injury to develop guidelines to aid clinicians in further management of these patients.